Bioenergetic shift and proteomic signature induced by lentiviral-transduction of gfp-based biosensors - Barakat, Sarah; Çimen, Şeyma; Miri, Seyed Mohammad; Vatandaşlar, Emre; Yelkenci, Hayriye Ecem; San Martín, Alejandro; Beker, Mustafa Çağlar; Kök, Kıvanç; Öztürk, Gürkan; Eroğlu, Emrah (My University, 2024)
Fluorescent proteins (FPs) stand as pivotal tools extensively employed across diverse biological research endeavors in various model systems. However, long-standing concerns surround their use due to the numerous side effects associated with their expression. Recent investigations have brought to light the significance of hydrogen peroxide (H2O2) that is associated with the maturation process of green fluorescent protein (GFP) fluorophores. The structural and functional impairments associated with GFP expression are possibly linked to this amount of H2O2. In this study, we assess the impact of the GFP-based HyPer7 biosensor on cellular homeostasis and proteome changes, aiming to identify potential risks related to oxidative stress responses that potentially risks the application of such tools. Cells expressing genome-integrated HyPer7 demonstrated altered mitochondrial membrane potential (MMP), which was alleviated by the addition of antioxidants or culturing cells at physiological normoxia (5 kPa O2). Additionally, HyPer7-expressing cells also exhibited significant impairment in mitochondrial oxidative respiration, suggesting broader mitochondrial dysfunction. Through untargeted proteomics analysis, we identified 26 proteins exhibiting differential expression in HyPer7-expressing cells compared to respective control cells. Functional annotation analysis showed that the list of the delineated proteins is associated with cellular responses to stress and the regulation of antioxidant mechanisms. Our findings underscore the significance of caution and validation in ensuring a thorough comprehension of cellular responses when using fluorescent protein-based tools, thereby enhancing the reliability of the results.
Keywords: Green Fluorescent Proteins; Hydrogen Peroxide; Hyper7 Genetically Encoded Biosensor; Oxidative Stress; Proteomic Signature